PERUBAHAN KESEMPATAN KERJA PEREMPUAN DI JAWA - BALI 1980 - 2003 - Tukiran Tukiran (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2005)
When Total Fertility Rate is getting lower, some even reach below the replacement level, the opportunity for women to enter the labor market is getting bigger. They are well educated so it is natural that labor participation rate is increasing too. But on the contrary, the employment opportunities is limited and caused a part of them to become an open unemployment and underemployment. Por those who already work, most of them work in non- agricultural sectors as half skilled manpower in other sectors. por the last 25 years, there has been a change in labor market for women, but there is still a wage gap between men and women for the same job.